Error Analysis in Descriptive Text Compositions of Seventh-Grade Students at SMP N 1 Gatak Sukoharjo - Siti Nur Arofah; Yunus Sulistyono (Universitas Muhammadiyah Surakarta, 2025)
Language errors are defined as violations or deviations from established language norms and rules. In practice, students' written work in the form of essays can be evaluated based on content, accuracy in word choice, sentence structure, and spelling. Based on this premise, the present study aims to identify the quality of students' descriptive text writing and the types of language errors that occur among students. This research employs a qualitative approach with a case study design. The subjects of the study were seventh-grade students at SMP N 1 Gatak, and the data consisted of students' descriptive texts. The findings indicate the presence of various language errors in the descriptive essays produced by the seventh-grade students of SMP N 1 Gatak. These language errors can be classified into five categories: spelling errors, word formation errors, morphological errors, and syntactic and semantic errors. Overall, the findings demonstrate that students still require intensive training in grammar and spelling in order to produce essays with accurate structure and meaning. Therefore, Indonesian language instruction is expected to place greater emphasis on the contextual application of linguistic rules, enabling students not only to understand theoretical concepts but also to apply them effectively in producing well-structured and accurate written texts.